Dispersion of mean consecutive differences in single‐fiber electromyography increases diagnostic sensitivity for myasthenia gravis. Issue 6 (31st March 2021) - Kojima, Yuta; Shibuya, Kazumoto; Uzawa, Akiyuki; Kano, Hiroki; Nakamura, Keigo; Yasuda, Manato; Suzuki, Yo‐ichi; Tsuneyama, Atsuko; Suichi, Tomoki; Ozawa, Yukiko; Misawa, Sonoko; Noto, Yu‐ichi; et al.
Abstract: Introduction: In this study we aimed to investigate the dispersion of mean consecutive difference (MCD) of concentric needle jitter studies of patients with myasthenia gravis (MG) and its effect on diagnostic sensitivity for MG. Methods: One hundred fifty‐three patients, including 76 patients with MG and 77 controls with possible MG who later received another diagnosis, underwent stimulated concentric needle jitter studies of the frontalis muscle. MCD mean, standard deviation (SD), and coefficient of variation (CV) were calculated. Diagnostic sensitivity and specificity were determined using receiver operating characteristic (ROC) analyses. Results: MG patients showed a significantly greater MCD mean (MG: control, 26.3 μs; 13.5 μs [median]; P  < .0001), MCD SD (MG: control,  12.8 μs; 5.1 μs [median]; P  < .0001), and MCD CV (MG: control,  46.1; 37.5 [median]; P  < .001) than those without MG. An ROC curve of SD showed a large area under the curve (0.88), and a cut‐off value of 7.2 μs, which was calculated by maximum Youden index, exhibited high diagnostic sensitivity (86%) for MG. Combined MCD mean, outliers, and SD criteria showed higher sensitivity (88%) than conventional criteria alone (82%), at the expense of lower specificity. Five MG patients with normal MCD mean and abnormal MCD SD had only ocular symptoms. Discussion: The dispersion of MCD as measured by MCD SD greater than 7.2 μs is significantly increased in patients with MG and may be a useful measure of abnormal jitter in the diagnosis of MG, especially for identifying patients with mild disease.